Analysis of DVB-T2 TV Broadcast Receiver with Comparison of Signal Reception Quality - Dzikrillah, Muhammad; Handayani, Ade Silvia; Rakhman, Abdul (PROtek : Jurnal Ilmiah Teknik Elektro, 2024)
Television is one of the most widely used media for receiving sound and image transmissions worldwide, particularly in Indonesia. Government regulations require all television broadcasters in Indonesia to cease analog broadcasts and transition to digital broadcasts. Consequently, a device known as the Set Top Box (STB), equipped with a low noise amplifier (LNA), converts DVB-T2 digital signals into images and audio suitable for analog televisions. Tests were conducted to evaluate its signal reception capabilities. These tests took place at four Palembang city locations, utilizing indoor and outdoor antennas. The results revealed that the device's signal strength ranged from -48.7 dBm, reaching 100% signal quality, to the weakest signal at -97 dBm. Moreover, an average difference of 6.9 dB was observed between indoor and outdoor testing for each frequency. Furthermore, analyzing the average signal strength based on distance showed that the highest strength of -56.2 dBm occurred at a distance of 1.5 km from the transmitter during outdoor testing. In comparison, the weakest strength of -91.6 dBm occurred at a distance of 1.8 km during indoor testing. Additionally, a signal strength comparison between test locations indicated that the most significant difference was between the Kamboja and Plaju locations. The LNA device achieved its highest gain value of 15.2 dB. Various factors, including antenna direction, obstructions such as buildings, antenna height, signal stability, and the distance between the transmitter and receiver, influence the signal quality.